Think Java How To Think Like a Computer Scientist - Mayfield, Chris; Downey, Allen; Open Textbook Library (Open Textbook Library, 2020)
Think Java is a hands-on introduction to computer science and programming used by many universities and high schools around the world. Its conciseness, emphasis on vocabulary, and informal tone make it particularly appealing for readers with little or no experience. The book starts with the most basic programming concepts and gradually works its way to advanced object-oriented techniques. In this fully updated and expanded edition, authors Allen Downey and Chris Mayfield introduce programming as a means for solving interesting problems. Each chapter presents material for one week of a college course and includes exercises to help you practice what you've learned. Along the way, you'll see nearly every topic required for the AP Computer Science A exam and Java SE Programmer I certification.
Preface -- 1 Computer Programming -- 2 Variables and Operators -- 3 Input and output -- 4 Methods and Testing -- 5 Conditionals and logic -- 6 Loops and Strings -- 7 Arrays and References -- 8 Recursive Methods -- 9 Immutable Objects -- 10 Mutable Objects -- 11 Designing Classes -- 12 Arrays of Objects -- 13 Objects of Arrays -- 14 Extending Classes -- 15 Arrays of Arrays -- 16 Reusing Classes -- 17 Advanced Topics -- A Tools -- B Javadoc -- C Graphics -- D Debugging
In English.
Description based on print resource
Keywords: Computer Science -- Textbooks; Programming Languages -- Textbooks